Strategi Guru PAI dalam Pembentukan Akhlak Siswa melalui Pengelolaan Pembelajaran dan Budaya Religius di MTs Darussalam Al Mubarok Cianjur - Diansyah Permana; Siti Rohmah; Dina Noviani; Maswiyah; Syifa Ramdani Faujiah (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
This study examines the strategies implemented by Islamic Education (PAI) teachers in shaping students’ moral character through the management of learning and the strengthening of a religious school culture at MTs Darussalam Al Mubarok Cianjur. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation to understand how pedagogical planning, classroom management, and religious habituation programs support character formation. The findings reveal that PAI teachers employ three integrated strategies: exemplary behavior, habituation of religious practices, and affective approaches that build emotional closeness with students. These strategies are reinforced by a well-managed religious school environment, principal support, and structured programs such as daily Quran recitation, congregational prayers, and routine mentoring. Challenges encountered include variations in student motivation and limited instructional time. Overall, the study highlights that effective learning management combined with a strong religious culture plays a crucial role in fostering students’ Islamic morals and disciplined behavior. Penelitian ini mengkaji strategi yang diterapkan guru Pendidikan Agama Islam (PAI) dalam membentuk akhlak siswa melalui pengelolaan pembelajaran dan penguatan budaya religius di MTs Darussalam Al Mubarok Cianjur. Menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui observasi, wawancara, dan dokumentasi untuk memahami bagaimana perencanaan pembelajaran, manajemen kelas, serta program pembiasaan religius mendukung proses pembinaan akhlak. Hasil penelitian menunjukkan bahwa guru PAI menerapkan tiga strategi yang saling terintegrasi, yaitu keteladanan, pembiasaan praktik keagamaan, dan pendekatan afektif yang membangun kedekatan emosional dengan siswa. Strategi tersebut diperkuat oleh budaya madrasah yang religius, dukungan kepala madrasah, serta kegiatan terstruktur seperti tadarus harian, salat berjamaah, dan pembinaan rutin. Adapun hambatan yang dihadapi meliputi perbedaan motivasi siswa dan keterbatasan waktu pembelajaran. Secara keseluruhan, penelitian ini menegaskan bahwa pengelolaan pembelajaran yang efektif dan budaya religius yang kuat berperan penting dalam pembentukan akhlak Islami siswa.